NZCrunchies: Crunchielicious By AinSyahirah / Wan Nur Ain Syahirah Wan Ishak - Wan Ishak, Wan Nur Ain Syahirah (2021)
This report is about the NZCrunchies business that has been conducted on social media, namely on the Facebook platform. I have created a Facebook to upload the business to be implemented. So, I have created a Facebook Page with the name Crunchieliciouns by AinSyahirah. For this task I need to post some elements such as teaser, hard sell, and soft sell.